2021
DOI: 10.1186/s13011-021-00421-7
|View full text |Cite
|
Sign up to set email alerts
|

Frequencies of emergency department use and hospitalization comparing patients with different types of substance or polysubstance-related disorders

Abstract: Background This study measured emergency department (ED) use and hospitalization for medical reasons among patients with substance-related disorders (SRD), comparing four subgroups: cannabis-related disorders, drug-related disorders other than cannabis, alcohol-related disorders and polysubstance-related disorders, controlling for various clinical, sociodemographic and service use variables. Methods Clinical administrative data for a cohort of 22,4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 94 publications
3
14
0
Order By: Relevance
“…Patients with serious MD are recognized as frequent acute care users [ 32 , 33 ]. Studies have shown that SRD, particularly polysubstance-related disorders (64% of the sample), increase the risk of co-occurring MD [ 34 ] and severe chronic physical illnesses [ 35 ], contributing to acute care use [ 36 ]. Suicidal behaviors were also elevated in the cohort at around 16%.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with serious MD are recognized as frequent acute care users [ 32 , 33 ]. Studies have shown that SRD, particularly polysubstance-related disorders (64% of the sample), increase the risk of co-occurring MD [ 34 ] and severe chronic physical illnesses [ 35 ], contributing to acute care use [ 36 ]. Suicidal behaviors were also elevated in the cohort at around 16%.…”
Section: Discussionmentioning
confidence: 99%
“…Profile 3 also had the highest percentage of patients with frequent ED use and hospitalizations, roughly twice the percentage found in Profile 1. Chronic SRD [ 8 ], serious MD [ 59 , 60 ] and personality disorders [ 61 ] have been found to increase the risk of frequent ED use and hospitalizations. A majority of patients in Profile 3 also lived alone or were single parents, conditions usually related to more adverse outcomes [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…More intensive and continuous outpatient care by various health professionals is usually required for patients affected by multimorbidity [ 7 ]. Patients with SRD are often affected by co-occurring chronic physical illnesses and mental disorders (MD), increasing the risk of acute care use [ 8 ] and premature death [ 9 ]. SRD also increases the risk of death by accident, suicide, or homicide [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive alcohol use in the United States was estimated to cause an average of 80,000 deaths each year and cost states a median of $2.9 billion in 2006 3 . Also, usage of emergency departments and hospitalizations was highest among those with alcohol-related disorders when compared to other substance-related disorders 4 . Looking at hospital emergency department data, alcohol usage has shown to be a main risk factor for morbidity and mortality in relation to both intentional and unintentional injury 5 , particularly in violence-related injuries 5 .…”
Section: Introductionmentioning
confidence: 93%